Menakar Lembaga Antikorupsi: Studi Peninjauan Kinerja Komisi Pemberantasan Korupsi - Suyatmiko, Wawan Heru; Nicola, Alvin (Komisi Pemberantasan Korupsi, 2019)
There is no universal standard in establishing and operating an ideal anti-corruption institution (ACA). Since 2013, Transparency International has developed a measurement tool that can capture the effectiveness of ACA’s performance in accordance with UNCAC's mandate and the Jakarta Principles. One of the main aspects is whether the ACA is in a supportive environment or is in a policy situation that impedes the implementation of anti-corruption laws. This study specifically seeks to review the strengths and weaknesses of Indonesian ACA, the Corruption Eradication Commission (KPK), based on TI’s measurement tools above, through 6 dimensions spread across 50 indicators over the 2016-2019 period. The study found that the KPK had strong and supportive environmental factors, both internally and externally, but has some notable exceptions in the aspect of independence. ACA’s performance measurement, whether carried out internally or externally, is significant to strengthen ACA independence and law enforcement in the long run.